Prospects for financial support for physical culture and sports in the Sverdlovsk Region - Polyakova E.Yu. ,; Lvova M.I. ,; Naboychenko E.S. ,; Yuzvovich L.I. ,; Knyazeva E.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the development of theoretical and methodological aspects of regional financing of physical culture and sports, taking into account trends in the budgetary provision of these expenses in the Russian Federation. Methods and structure of the study. System-structural, functional, factorial and comparative methods of analysis were used with the construction of analytical models based on the synthesis of modern scientific methods of cognition of economic and social phenomena. Results and conclusions. The article discusses the reasons for the growth, subsequent decline and prospects for the development of physical culture and sports in the Sverdlovsk region in the coming years. It is noted that sustainable economic development in this area is impossible without attracting more extra-budgetary sources, which currently does not meet the target. This issue becomes especially acute in anticipation of the sequestration of regional budget expenditures on physical culture and sports in 2023-2025, which confirms the relevance of the study.